ASIMILASI NILAI KEKELUARGAAN LINTAS ETNIK - Wanto Rivaie (Jurnal Ilmiah Visi, 2011)
Indonesian people comprises of a lot of ethnic groups and some of them stay and live together sharing the same area. As each of the ethnic groups has specific culture and value, this research wanted to know how the value of family relationship assimilated across the ethnic groups, particularly among Dayaks, Melayunese, and Javanese transmigrants in Rasau Jaya village, Kubu Raya District, West Kalimantan. The research conducted in 2010 aimed at identifying, describing, and analyzing the cross ethnic assimilation process of the family relationship value. To meet the purpose of the research, analysis model based on Peter Blau’s theory was employed and descriptive naturalistic method was used. The data were collected by using interview, structured observation, and document study techniques. The result of the research indicates that cross ethnic assimilation of family relationships value are done through value transformation and implementation, family union, appropriate moral value, democracy, togetherness, and solidarity. Various ethnic cultural backgrounds do not hinder the establishment of harmonious life of the ethnic groups. Based on the findings, the research provides a set of recommendations for the policy makers and further research.